Incorporação de amora na elaboração de cerveja artesanal - Trindade, Simone Cezar (2016)
Over the last decade has been noted significant growth in the production of craft beer worldwide. By the increased purchasing power and the cultural changes of the population, consumers are becoming more demanding and interested in learning about the processes involved in the manufacture of food. With the infinite number of adjuncts that can be incorporated into the beer-making process, it is possible to obtain different products with specific characteristics. Aiming to this new demand for craft beers, the purpose of this research was to test the incorporation of blackberry fruit Cv. Tupy in the manufacturing process of craft beer unpasteurized, to develop a local product with high added value. Thus, four brewed beers were developed, with different concentrations of blackberry pulp (0, 10, 20 and 30%).The beverages were evaluated for their physical and chemical characteristics (total soluble solids, total titratable acidity, bitterness, color, total anthocyanins, phenolic compounds and antioxidant activity), and subjected to sensory evaluation (sensory ordering tests) to determine the intensity of the pink color, fruity odor and sensory preference. The blackberry addition resulted in more acidic beers, as well as higher antioxidant activity, resulting from the migration of substances present in the fruit. The beer produced with 20 and 30% of blackberry pulp are more preferred compared to traditional beer. From the results obtained, it can be concluded that the production of beer increased by blackberry pulp is presented as a possible alternative that allows producers to offer a higher value added product.